Humans, robots and values. (May 2016) - Cockshott, Paul; Renaud, Karen
Abstract: From the 1950s onwards the threat automation posed to human labour became a persistent theme in popular science fiction[26, 1] . Authors explored what it meant to be human, by contrasting us with hypothetical robots. Such robots were generally seen as coming into existence centuries into the future. In the last decade the rate of progress in robotics has accelerated way beyond popular expectation. The timescales of Asimov and Dick look generous, whereas the dystopian near future of 'Player Piano'[71] seems grimly real. This anxiety is not limited to novelists. Even Stephen Hawkins told the BBC:"The development of full artificial intelligence could spell the end of the human race."[11] . Robotics is made possible by advances in mechanical engineering but, above all, by informatics. In this essay we look at how ideas derived from informatics allow us a more precise view of what differentiates us from robots and, on the other hand, how information science can give us a deeper insight into the nature of human labour. Having gained this understanding, we can go on to examine what sort of threat robots really pose to us, as humans. Highlights: Development of two concepts of work in the Scottish enlightenment those of Smith and Watt. Smiths Labour theory of value and its relation to Turing's idea of the universal machine, universality of labour. Adequacy/inadequacy of Marx's conceptualisation of labour in the light of Darwin and later biology. Relation of robots to Turings concept of the universal computer. Relationship between human work and thermodynamics. Is a workerless capitalist economy feasibile, work of Turing and von Neumann, implications for value and profit of industry.